Problem-based learning: Generates higher-order thinking skills of tenth graders in ecosystem concept - Ramdiah, Siti; Abidinsyah, H.; Mayasari, Ria (Jurnal Pendidikan Biologi Indonesia, 2018)
This study aimed to determine the effect of Problem-Based Learning (PBL) model on tenth grade studentsâ higher-order thinking skills (HOTS) in ecosystem concept. The design of this study was quasi experimental research with "nonequivalent pretest-posttest control group design". The population of this study was X grade students in Senior High School (SHS) Kandangan, South Kalimantan. The sample were chosen through random sampling technique. The sample will be tested for equivalence based on the data of from the report card from the first semester. The instrument of data collection is students HOTS rubric that developed by Hart (1994) with a range of scores for each question ranging from 0 to 4. One way analysis of variance (anava) was used as hypothesis test in this study. The result showed that PBL learning model had a positive effect on HOTS. It can be seen from the average of HOTS level of control class was 28.40 and treatment class was 36,23 and seen from F value = 20.97 whereas F table = 0.05 means F arithmetic > F table.